Recent advances in NIR-II fluorescence based theranostic approaches for glioma - Li, Jiaying; Ling, Jue; Yao, Chaoyi (Frontiers in Chemistry, 2022)
Gliomas are among the most common malignant tumors in the central nervous system and lead to poor life expectancy. However, the effective treatment of gliomas remains a considerable challenge. The recent development of near infrared (NIR) II (1000–1700 nm) theranostic agents has led to powerful strategies in diagnosis, targeted delivery of drugs, and accurate therapy. Because of the high capacity of NIR-II light in deep tissue penetration, improved spatiotemporal resolution can be achieved to facilitate the in vivo detection of gliomas via fluorescence imaging, and high contrast fluorescence imaging guided surgery can be realized. In addition to the precise imaging of tumors, drug delivery nano-platforms with NIR-II agents also allow the delivery process to be monitored in real-time. In addition, the combination of targeted drug delivery, photodynamic therapy, and photothermal therapy in the NIR region significantly improves the therapeutic effect against gliomas. Thus, this mini-review summarizes the recent developments in NIR-II fluorescence-based theranostic agents for glioma treatment.